Fuel-efficient attitude maneuvers of flexible spacecraft with residual vibration reduction into an expected level - Parman, Setyamartana; Koguchi, Hideo (Computer Assisted Methods in Engineering and Science, 2000)
A three-dimensional rest-to-rest attitude maneuver of a satellite with flexible solar panels equipped by on-off reaction jets is studied. Results indicate that, under an unshaped input, the maneuver induces an undesirable motion of the satellite as well as vibration of the solar panels. Fuel-efficient input shapers are then applied to reduce the residual oscillation of its attitude. By reducing vibrations at several large-amplitude natural frequencies, the expected pointing precision of the satellite can be satisfied.